Zambia : Technical Assistance Report-Towards an Integrated Legal Framework for Public Financial Management. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Technical Assistance report proposes a roadmap for completing the process of drafting and adopting an Integrated Legal Framework for Public Financial Management (PFM) in Zambia. The legal framework for PFM in Zambia is fragmented, and much of it is outdated. The government has prioritized a revision of the existing legal framework for PFM and national development planning. This revision will permit a range of important PFM reforms that are ongoing or planned to be incorporated within the legal framework. An updated legal framework would also permit other important improvements in current practices to be incorporated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet